Wydatki na wdrożenie nowych regulacji prawnych w zakresie ochrony danych osobowych na przykładzie wybranej gminy - Długozima, Marek (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
In connection with the obligation of direct application by the member states of the European Union of European Parliament and Council Regulations, entities processing personal data are obliged, from May 2018, to comply with the new standards set in General Data Protection Regulation (EU) 2016/679 from 27th April 2016 on data protection and privacy for all individuals, free flow of such data and on superseding the Data Protection Directive 95/46/EC). In the article the direct costs of necessary adaptation activities were estimated as well as expenditure on infrastructure operated by the studied municipality, mainly IT.
Keywords: personal data protection; costs of doing business; GDPR; local government units; cost accounting